PERANCANGAN SISTEM INFORMASI PRODUKSI DEPARTEMEN ASSEMBLING BERBASIS VISUAL BASIC.NET DAN MICROSOFT ACCESS DI PT JONAN INDONESIA - Kurnia, Okto; Putra, Rani Laple Satria; mulyanto, ali (SAINTEKBU, 2021)
Supply of goods information system at jonan indonesia is use running has using the computer but it is use only in the field of administration while the marketing still used the manual wraiting .There fore it is necessary to computer based information system supply of goods better sofware .The aimed for this supply of goods informatin system simplify the processing of supplier data in detail , precise and accurate. The metods of data collection used is by doing observation and interview and is equipped with a literature review that has a close relevance to the subject matter. Microsoft visual studio 2010 was chosen to be a software in making the information system of home supply of goods and using microsoft acces 2007 database.This supply of goods information system is made to facilitate the administrative work of consumer data because data received administration is computerized . The suggestion given is to develop and refine this system to complete the existing facilities.